A B2 szintű nyelvtudás elérése és igazolása a felsőoktatásba történő felvételihez: Nyelvtanárok véleménye egy kérdőíves felmérés eredményeinek tükrében - Öveges, Enikő; Kálmán, Csaba (Magyar Pedagógia, 2019)
In spite of the fact that speaking a foreign language has become a key competence in Hungary by the millennium, there is still a strong necessity to develop language education in the country in 2020, especially if we consider the data pertinent to the foreign language proficiency of school children and adults alike. Our article presents the findings of an online survey, one focus of which was to measure and explore Hungarian secondary school language teachers’ opinions of a recent language policy measure that was meant to remedy and improve the regrettable situation described above. The measure stipulated that certifying a B2 foreign language proficiency would be a prerequisite of admission to higher education in Hungary from 2020 onwards. Even though the provision has been withdrawn in the meantime, it has generated such widespread professional and social debates that the findings of the survey are nevertheless intriguing. The online questionnaire – consisting of Likert scale statements and open-ended questions concerning the 2020 requirement – was filled in by 960 language teachers working in grammar schools and technical secondary schools in Budapest, other county seats and smaller towns in Hungary. The results have revealed that despite the language lessons and preparatory courses that several secondary schools offer to their students in order to meet the above requirement, the majority of learners are not ready to fulfil such a precondition. The participants of the survey cite the lack of central help primarily which prevents them from meeting the prerequisite both on an individual and institutional level. The smaller the settlement, the greater the extent of help they call for. Many of the language teachers are concerned that the measure would decrease equal opportunities for socially, geographically, and economically disadvantaged school children. Another major worry the participants highlight is that students talented in a diverse range of professions would not be admitted to tertiary education if the provision came into force. Based on the results, it can be concluded that if the measure were ever to be introduced, both language teachers and secondary schools, especially technical secondary schools and schools in smaller settlements, would require more information and more substantial support.